Aplikasi E-Learning pada SMK Negeri Kundur Berbasis Web - Ade Winarni; Yafri; Reno Kurniawan (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2017)
The development of highly advanced technology in the modern era and globalization allows various activities to be carried out quickly and efficiently. Technological developments have had an influence on the way of life of humans, one of which is in the field of education with the use of e-learning in learning activities in schools and colleges. E-learning (electronic learning) is a learning concept that is carried out through media networks designed with media that can be accessed from computer terminals or different devices that are compatible with technological means that can access websites on a web browser with an Internet network. SMK Negeri Kundur is a public education institution that provides vocational education at the secondary education level as a continuation of SMP / MTS with agribusiness expertise programs in plantation crop production, agricultural mechanization, computer informatics engineering, electronic engineering, and building engineering which is located on Jl.Besar Sawang Km. .14 ​​Kel. Sawang Selatan, Kec. Kundur Barat. SMK Negeri Kundur is one of the educational institutions that still uses conventional methods as a learning process, where the learning method is carried out face-to-face between teachers and students, the use of technology in classrooms such as computers and other multimedia tools is limited to subjects that need it, as well as teaching materials in the form of a printed text book. Based on the author's observations made at SMK Negeri Kundur, the problem posed by SMK Negeri Kundur is the limited interaction between students and teachers in the classroom due to the teaching and learning process taught by learning hours at school, the limited teaching materials in the form of printed books, causing students find it difficult to understand the subject matter. Therefore, the authors are interested in creating a web-based e-learning application. With the use of e-learning at SMK Negeri Kundur, it is hoped that it will solve the problem of limited student learning hours at school and the limited teaching materials that are still in the form of printed textbooks, because e-learning can be used as a learning support tool that can be accessed anytime and anywhere and eliminating limits on learning hours at school so that it can streamline and complement those of conventional learning methods.